PREVALENCE OF TOXOPLASMA GONDII IN BIRDS OF KERMAN CITY BY SEROLOGICAL AND PARASITOLOGICAL METHODS - H. Keshavarz Valian ; A. Ebrahimi (Tehran University of Medical Sciences, 1994)
A Total of 332 birds including 149 sparrows, 147 doves and 36 pigeons were examined for Toxoplasma infection by both direct agglutination for detecting antibodies to Toxoplasma and direct parasitological test to detect the cyst of Toxoplasma in the brain of birds. The Toxoplasma sero-positive rate (SPR) in the examined birds was 10.5 percent (27 cases) with titers of 1:40 or higher and SPR in each group tested were 17 percent in sparrow; 5.1 percent in doves and 2.8 percent in pigeons. The SPR between sparrows and doves and also between sparrows and pigeons were significantly different (P